Factors influencing entrepreneurs intention to pay zakat: evidence from Kano Nigeria. A conceptual frame work - Muhammad, Sani Adamu; Saad, Ram Al Jaffri (2016)
Entrepreneurs contribute immensely to the development of many countries.Whether the country is developed, developing or underdeveloped, entrepreneurs played significant role in employment provision and contribution to Gross Domestic Product.Despite the contribution of Small and Medium Enterprises to development of many countries, poverty in developing and underdeveloped countries is at the high level. Therefore, the main objective of this study is suggest a model that will address factors influencing entrepreneur’s intention to pay zakat in Kano Nigeria.The important of zakat for poverty reduction in Islam cannot be quantify. Zakat refers to the determined portion of wealth recommended by Allah SWT for distribution among the deserving classes of those permitted to receive it. However, zakat collection in Kano Nigeria is still at low level.The paper proposes a model which if validated empirically will be used for policy making by Kano state Zakat and Hubsi commission, Government, Zakat payers among others. Understanding factors that will influence intention to pay zakat might be an important contribution to knowledge.